Comparison of Mathematics Learning Outcomes of Students in Auditory Intellectually Repetition (AIR) and Reciprocal Teaching (RT) Learning Models - Sufri Mashuri; Jahring Jahring; Nasruddin Nasruddin; Hasan Djidu (Journal of Educational Science and Technology (EST), 2020)
The purpose of this study is to see the differences in the mean increase in student mathematics learning outcomes in the Auditory, Intellectually, Repetition (AIR) model and reciprocal teaching (RT) model. The sample in this study were 25 students as the experimental class 1 and 23 students as the experimental class 2. This research was an experimental study with a nonequivalent control group design. The data analysis used was descriptive and inferential analysis. The results of the descriptive analysis showed that the mean pretest score of the experimental class 1 was 51.64 and the posttest result was 70.88 with the increase in student mathematics learning outcomes reaching 0.39. While the mean pretest score of experimental class 2 was 36.52 and the posttest result was 70.48 with the increase in student mathematics learning outcomes reaching 0.51. The variance of the increase in mathematics learning outcomes in the experimental class 1 was 0.02, and the experimental class 2 was 0.01. The results obtained indicate that the increase in mathematics learning outcomes through the reciprocal teaching learning model is higher than the increase in student mathematics learning outcomes using the AIR learning model.